Discovery of Novel Antimalarial Drugs Based on Thiosemicarbazone Derivatives: An In Silico Approach - Anant, Arjun; Kaur, Kamalpreet; Asati, Vivek (Current Signal Transduction Therapy, 2022)
Background: Thiosemicarbazones belong to the group of semicarbazides, which contains a sulfur atom instead of an oxygen atom. Several studies have shown that they are effective against extracellular protozoans like Trichomonas vaginalis, Plasmodium falciparum, Trypanosoma cruzi, and other parasites. Objective: The current research involves pharmacophore model design, 3-D-QSAR, virtual screening, and docking studies, all of which are evaluated using various parameters. Methods: The present study was performed by Schrodinger software. A total of 40 ligands were selected for the development of 3D QSAR models. To predict the pIC50 values in 3D-QSAR analysis, the entire dataset was divided into two sets, training, and test sets, in a 7:3 ratio. The selected pharmacophore hypothesis has been used for the virtual screening study. Results: DHHRR_1 emerged as the best pharmacophore model with a survival score of 5.80. The 3D QSAR study showed a significant model with R2 = 0.91 and Q2 = 0.73. The series top-scoring compound 7e had a docking score of -10.44 and showed interactions with the amino acids, ARG- 265, PHE-227, and LEU-531, required for activity. The developed pharmacophore model had been used for the screening of ZINC compounds, where ZINC26244107, ZINC13469100, ZINC01290725, and ZINC01350173 showed the best XP docking scores (-11.60, -11.27, -11.35, - 10.52, respectively) while binding important amino acids ARG265, HIE185 and LEU 531 against plasmodium falciparum, PDB ID:5TBO. The docking study was further evaluated by taking standard drug chloroquine, showing similar binding interactions as shown by other compounds. The ADME studies showed the drug-likeness properties of the compounds. Conclusion: The results of the present study may be helpful for the future development of antimalarial compounds against Plasmodium falciparum.
Keywords: 3-D QSAR